An Analysis Of Illocutionary Act By The Main Character In The Turning Red Movie - Futri Rahayu; Galuh Dwi Ajeng; Aksendro Maximilian (Institute of Research Institutions and Community Service (LPPMP) of STKIP PGRI Bandar Lampung, 2026)
This research aims to analyze the illocutionary acts performed by the main character, Meilin